Functional Age-Related Changes Within the Human Auditory System Studied by Audiometric Examination - Profant, Oliver; Jilek, Milan; Bures, Zbynek; Vencovsky, Vaclav; Kucharova, Diana; Svobodova, Veronika; Korynta, Jiri; Syka, Josef (Frontiers in Aging Neuroscience, 2019)
Age related hearing loss (presbycusis) is one of the most common sensory deficits in the aging population. The main subjective ailment in the elderly is the deterioration of speech understanding, especially in a noisy environment, which cannot solely be explained by increased hearing thresholds. The examination methods used in presbycusis are primarily focused on the peripheral pathologies (e.g., hearing sensitivity measured by hearing thresholds), with only a limited capacity to detect the central lesion. In our study, auditory tests focused on central auditory abilities were used in addition to classical examination tests, with the aim to compare auditory abilities between an elderly group (elderly, mean age 70.4 years) and young controls (young, mean age 24.4 years) with clinically normal auditory thresholds, and to clarify the interactions between peripheral and central auditory impairments. Despite the fact that the elderly were selected to show natural age-related deterioration of hearing (auditory thresholds did not exceed 20 dB HL for main speech frequencies) and with clinically normal speech reception thresholds (SRTs), the detailed examination of their auditory functions revealed deteriorated processing of temporal parameters [gap detection threshold (GDT), interaural time difference (ITD) detection] which was partially responsible for the altered perception of distorted speech (speech in babble noise, gated speech). An analysis of interactions between peripheral and central auditory abilities, showed a stronger influence of peripheral function than temporal processing ability on speech perception in silence in the elderly with normal cognitive function. However, in a more natural environment mimicked by the addition of background noise, the role of temporal processing increased rapidly.